In vivo comparison of small- and large-bore aspiration catheters in patients with ST elevation myocardial infarction - Katarzyna Pigoń; Maciej Pękała; Natalia Tomecka; Edyta Radzik; Ewa Nowalany-Kozielska; Andrzej Tomasik (Śląski Uniwersytet Medyczny w Katowicach, 2023)
INTRODUCTION: Aspiration thrombectomy is recommended only in selected patients with ST elevation myocardial infarction (STEMI). Optical coherence tomography analysis revealed limitations of some aspiration catheters in thrombus removal. Additionally, in vitro tests show significant differences in their effectiveness depending on the design of the distal tip and their internal diameter. The aim of this study is to compare the results of percutaneous coronary intervention (PCI) alone and adjunctive aspiration thrombectomy using catheters with small and large cross-sectional areas, compare the effectiveness of coronary angioplasty with and without aspiration thrombectomy, as well as check the effectiveness of different catheters depending on their internal diameter. MATERIAL AND METHODS: 773 patients with STEMI were enrolled in the study: 586 patients with PCI alone (Ctrl group), and 187 patients with PCI and aspiration thrombectomy. All the aspiration catheters were categorized as large-bore - 146 patients (LB group) and small-bore - 41 patients (SB group). Myocardial perfusion, left ventricular ejection fraction (LVEF) and the long-term all-cause mortality were compared. Statistical analysis was based on non-parametrical, ANOVA and Kaplan-Meier survival analysis. RESULTS: The groups were significantly biased with respect to demographics and the angiographic presentation of myocardial infarction. In comparison with the Ctrl group the LB and SB groups were younger and presented worse epicardial flow and thrombus burden according to the Thrombolysis in Myocardial Infarction (TIMI) classification. There is an insignificant trend towards inferior myocardial perfusion in the SB group in comparison with the Ctrl group. The LB group had a lower pre-discharge LVEF in comparison to the Ctrl group. The long-term all-cause mortality was comparable across the groups. CONCLUSIONS: There is not enough evidence to prove that SB catheters are less effective. A positive observation is the fact that the long-term all-cause mortality in the group of patients with adjunctive aspiration thrombectomy is comparable to the control group. However, this observation requires confirmation in future studies.